Intraoperative methods for detecting bile leakage for liver resection: Current situation - Shu-Tian Mo; Tao Peng (Journal of Nutritional Oncology)
Abstract. Bile leakage is one of the common complications after hepatectomy. Recalcitrant bile leakage not only seriously affects the quality of life of patients, but also prolongs the hospitalization time, increases hospitalization costs, and puts psychological, mental, and financial pressure on patients. The most commonly used methods for the surgical detection of bile leakage include the White test, developer injection through the gallbladder tube/gallbladder, and photodynamic imaging. A new method, Peng’s leakage test, was developed by the authors to detect bile duct leakage and was shown to be the best method available to prevent postoperative bile leakage in patients.